Application of Islamic Insurance (Takaful) as a panacea to the present Economic Downturn in Northern Taraba State, Nigeria - Haruna Dahiru; Lawan Abdullahi Muhammad; Steve Paul Anuye; Lawan Garba (Bulletin of Islamic Research, 2026)
Purpose – This study examines the application of Islamic insurance (Takaful) as a strategic mechanism for addressing the ongoing economic downturn in Northern Taraba State, Nigeria. The research explores the potential of Takaful to enhance economic resilience, promote financial inclusion, and support sustainable socio-economic development in a region characterized by agricultural vulnerability, insecurity, limited access to formal financial services, and unstable household incomes. Design/methodology/approach – The study adopts a mixed-methods approach, integrating quantitative and qualitative analyses. Data were examined to assess the role of Takaful contributions (tabarru’) in risk mitigation, livelihood protection, and business continuity among households and small and medium enterprises (SMEs). The analysis is further grounded in Islamic normative sources, including relevant Qur’anic injunctions and Prophetic traditions that emphasize mutual cooperation, solidarity, and ethical risk-sharing. Findings – The findings indicate that Takaful provides an effective alternative to conventional insurance by promoting collective responsibility, reducing financial vulnerability, and strengthening risk management mechanisms. Empirical evidence suggests that Takaful contributes to greater financial inclusion among Muslim communities, enhances economic empowerment, and supports the sustainability of household and business activities during periods of economic uncertainty. The principles of mutual assistance (ta‘āwun) and ethical financial participation emerge as key factors in fostering community resilience. Research implications/limitations – The study focuses on Northern Taraba State and may not fully capture the diverse socio-economic conditions of other regions. Future research may undertake comparative studies across different states or examine long-term impacts of Takaful adoption on poverty reduction and economic growth. Originality/value – This study contributes to the growing literature on Islamic finance by demonstrating the practical relevance of Takaful as a Shari’ah-compliant instrument for economic stabilization. It highlights the role of Islamic insurance in promoting equitable development, social protection, and financial sustainability within vulnerable communities.